The gearhead's guide to dirt bikes - Amstutz, Lisa J. (Amstutz, Lisa J. Gearhead guides., 2023)
Explores the different components of a dirt bike and offers advice for readers on how to upgrade and modify with different parts to make their dirt bikes faster and tougher. Includes photographs, sidebars, further reading suggestions, and a glossary.